Concentration on the few? R&D and innovation in German firms between 2001 and 2013 - Christian Rammer; Torben Schubert (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2016)
[Introduction] Innovation expenditures in Germany have increased at an impressive rate in the course of the last two decades. Between 1995 and 2013, businesses in Germany raised their spending for developing and introducing new products and new processes from exteuro60.8bn to exteuro144.6bn resulting in a compound annual growth rate of 4.9% (Rammer et al. 2015). While these numbers suggest that German firms have become ever more focused on innovation, they hide the fact that this rise has mainly been driven by large firms belonging to a few sectors. When we look at the above numbers by firm size we find that firms with fewer than 500 employees experienced only a very modest increase in their innovation expenditures ( exteuro25.7bn in 1995 vs. exteuro34.5bn in 2013, i.e. 1.6% per year) whereas large firms with more than 500 employees increased their spending from exteuro35.1bn in 1995 to exteuro110.1bn in 2013 (6.6% per year). In line with these observations we also find a concentration of the activities on fewer firms. In particular, the share of innovators – firms that have introduced at least one product or process innovation during the preceding three years – has similarly declined since the late 1990s. Having reached a peak in 1999 at 55.5%, it dropped to 43.7% in 2007 and further declined to 37.1% in 2013. A look at the sector distribution conveys a similar concentration. In 1995, the R&D intensive manufacturing sectors (pharmaceuticals, chemicals, electronics, machinery & equipment, vehicles) spent exteuro30.9bn on innovation and increased that figure to exteuro92.6bn in 2013 (+6.3% per year). Low-tech manufacturing and service sectors expanded their innovation expenditure by an average annual rate of 3.1%. These developments would not be problematic if they were due to firms from high-tech sectors growing at an above-average rate. While some well-known examples of this phenomenon also exist in Germany, e.g. the software company SAP, the absolute numbers of such cases is very limited. Moreover, the share of value added of highly R&D-intensive sectors has remained fairly stable in Germany. This makes this explanation implausible. [...]
urn:nbn:de:0011-n-3829352
Keywords: 330